A case study of software process improvement with CMMI‐DEV and Scrum in Spanish companies. Issue 12 (26th July 2013) - Garzás, Javier; Paulk, Mark C.
ABSTRACT One of the most commonly used agile methods is Scrum. Capability Maturity Model Integration for Development (CMMI‐DEV) is currently the de facto framework for process improvement and for determining the organizational maturity of software development companies. CMMI‐DEV and Scrum share certain characteristics, and even though they were developed for different purposes, they can be complementary to each other; and as such, they are not in competition. This paper presents a case study of the relationship between level 2 of CMMI‐DEV 1.3 and Scrum. This research has focused on the relationships between Scrum and level 2 of CMMI‐DEV 1.3. The objective of this research paper is to evaluate how Scrum helps implement a process model such as CMMI‐DEV. A detailed case study was conducted among Spanish IT companies. The case study was designed according to established guidelines for cases studies. There were eight principal activities: case study design, case selection, case study procedures and roles, data collection, analysis, plan validity, study limitations, and reporting. The results obtained show that most of the process areas of CMMI‐DEV level 2 had been improved by using Scrum. Other issues detected arose during the formal appraisals and illustrated how it is possible to verify with Scrum that the specific goals of CMMI‐DEV have been implemented. In addition, it highlights how the use of open‐source tools was useful in improving the process in the companies involved. Based on the case study carried out, the addition of Scrum methodologies may improve the increase in quality of software processes. Copyright © 2013 John Wiley & Sons, Ltd.